Association Between Enteral Nutrition Management And Glucose Stability Among Hospitalized Patients With Type 2 Diabetes Mellitus Patients: A Cross-Sectonal Study - Kartika Sari Wijayaningsih; Ernawati Ernawati; Andi Fajriansi; Nurafriani Nurafriani; Sitti Nurbaya; Alfiah Alfiah; Hasifah Hasifah; Shinta Arini Ayu (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Glucose instability is a common challenge among hospitalized patients with Type 2 Diabetes Mellitus (T2DM) and is associated with adverse clinical outcomes, including prolonged hospitalization, increased risk of complications, and higher healthcare utilization. Enteral nutrition management may play an important role in maintaining glycemic control during hospitalization; however, evidence regarding its association with glucose stability remains limited, particularly in Indonesian healthcare settings. To analyze the association between enteral nutrition management and glucose stability among hospitalized patients with Type 2 Diabetes Mellitus. An analytical observational study with a cross-sectional design was conducted in the inpatient ward of RSAU dr. Dody Sardjoto Hospital, Indonesia, from July to September 2025. Thirty hospitalized patients with T2DM who received enteral nutrition therapy for at least 72 hours were recruited using purposive sampling. Enteral nutrition management was evaluated based on formula appropriateness, energy adequacy, protein adequacy, feeding frequency, and feeding method. Glucose stability was assessed using the coefficient of variation (CV) of blood glucose measurements obtained during the first 72 hours of enteral nutrition therapy. Data were analyzed using Chi-square, Fisher’s Exact, and logistic regression tests with a significance level of p < 0.05. Ethical approval was obtained from the Health Research Ethics Committee of STIKES Notokusumo (No. 034/STIKES-NH/KEPK/V/2025). The participants had a mean age of 59.4 ± 3.1 years and a mean diabetes duration of 12.0 ± 3.8 years. Overall, 19 patients (63.3%) achieved stable glucose levels (CV < 36%), whereas 11 patients (36.7%) experienced glucose instability. Diabetes-specific enteral formulas were significantly associated with a higher proportion of glucose stability compared with standard polymeric formulas (p = 0.003). Enteral feeding administered 5–6 times daily was also significantly associated with better glucose stability than feeding frequencies of 3–4 times daily (p = 0.021). No significant association was observed between total daily energy intake and glucose stability (p = 0.074). In addition, the proportion of hyperglycemia was lower among patients receiving diabetes-specific formulas than among those receiving standard formulas. Diabetes-specific enteral formulas and more frequent enteral feeding schedules were associated with better glucose stability among hospitalized patients with Type 2 Diabetes Mellitus. These findings support the importance of optimizing enteral nutrition management as part of comprehensive glycemic care in hospital settings. Further prospective studies with larger sample sizes are warranted to confirm these findings.